Teknologi Pembelajaran Jarak Jauh dan Guru Pendidikan Agama Islam Studi Madrasah Ibtidaiyah Negeri 11 Aceh Tenggara - Harpan Reski Mulia (PAKAR Pendidikan, 2021)
This study aims to explore the barriers of Islamic education teachers in using learning technology when implementing distance learning at Islamic Elementary School 11 Southeast Aceh. The method used in this research is quantitative with a descriptive approach. The data were collected by means of survey and interviews, and the data analysis used was descriptive analysis. The sampling method in this study using the Krejcie and Morgan table (Krejcie Table) and random sampling. The Krejcie Table was used to draw samples to fill out a survey totaling 108 parents of students, and the random sample used to be interviewed directly consisted of 4 Islamic Education teachers and 6 students. This research found that there are several obstacles for Islamic education teachers in using technology that supports Islamic education learning. First, the obstacles that arise from students are the availability of facilities and awareness of students and parents in adapting to learning during the Covid-19 pandemic. Second, from Islamic Education teachers, namely the ability of teachers to use PAI technology and materials which put more emphasis on practice. This research has implications for Islamic education teachers to immediately upgrade their abilities in the use of educational technology, to parents of students to participate in providing assistance to students, especially in this pandemic condition, and to the functionaries of education policyl the implication of this research is to review the application of distance learning especially in the green zone.